Effects of once-weekly shallow water aerobic exercise on functional performance in elderly women - Veronika Kramperová; Michal Šteffl; Jan Heller (Karolinum Press, 2016)
The purpose of this study was to examine the effects of 24-week shallow-water aerobic exercise on functional performance in postmenopausal women. Thirty-seven women aged 60+ (mean age 67.2 ± 4.8 years) were self-selected to a water exercise group (n = 21) or to a comparison group (n = 16). The training consisted of a 24-week (60 min.day−1, 1 d.wk−1) supervised and guided exercise programme that included aerobic and strength training using an aquatic noodle in shallow water (1.2 m). Outcome measures were 30-s chair stand and 30-s arm curl tests, assessed at baseline and 24 weeks. Significant differences between groups were analyzed using Fisher's exact test. At 24 weeks there was a significantly (p < 0.05) greater improvement in measure of upper-body strength in the water exercise group. Arm curling improved by 15.8 versus 14.3% in the water exercise and comparison groups, respectively.